2008
DOI: 10.6090/jarq.42.231
|View full text |Cite
|
Sign up to set email alerts
|

Development of Rice Varieties for Whole Crop Silage (WCS) in Japan

Abstract: Over-production of rice has been a problem for the past 40 years in Japan. On the other hand, there is also a need for an increase in the production of domestic bulk feed in Japan. Whole crop silage (WCS) rice is being promoted by the government. The whole aerial parts consisting of grains, leaves and stems are harvested at the yellow ripening stage. At present, about 12 WCS rice varieties have been bred and are commonly used in Japan. The total digestible nutrients (TDN) yields of WCS varieties are 3 to 27% h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 5 publications
2
43
0
Order By: Relevance
“…The superior growth after transplanting might be attributed to their higher seedling dry weight (not shown) due to the large amount of accumulated carbohydrates at the time of transplanting (Honda and Usuda, 1959). The seedling vigor in these varieties might be associated with their grain size, which was much larger than the commercial cultivars (Kato, 2008), because the endosperm nutrients serve as a source for growth during the early seedling period (Sasaki, 2004). Murakami et al (1982) reported that seedlings with greater leaf number or greater ratio of shoot dry weight to length showed vigorous growth early after transplanting at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior growth after transplanting might be attributed to their higher seedling dry weight (not shown) due to the large amount of accumulated carbohydrates at the time of transplanting (Honda and Usuda, 1959). The seedling vigor in these varieties might be associated with their grain size, which was much larger than the commercial cultivars (Kato, 2008), because the endosperm nutrients serve as a source for growth during the early seedling period (Sasaki, 2004). Murakami et al (1982) reported that seedlings with greater leaf number or greater ratio of shoot dry weight to length showed vigorous growth early after transplanting at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not yet known whether SCI can explain genotypic differences in biomass productivity at low temperatures. On the other hand, whereas most of the high-yielding indica varieties are the semi-dwarf type, the recently released high-yielding japonica varieties developed not only to provide food for humans but also as livestock forage have long culms (Kato, 2008). Few studies have sought to evaluate the early growth of these high-yielding japonica varieties with different seedling characteristics compared to the semi-dwarf indica genotypes.…”
mentioning
confidence: 99%
“…In 2009, approximately 10,000 ha of forage rice was in cultivation. Over a dozen forage rice cultivars with high dry matter yield have been released and are grown commercially (Kato 2008, Sakai et al 2003, 2008.…”
Section: Background To Breeding Objectivesmentioning
confidence: 99%
“…While many paddy fields are fallow due to the overproduction of rice, the cultivation of livestock feed in paddy fields could improve the feed self-sufficiency ratio and make their use more effective. From this perspective, in Japan, paddy rice varieties for WCS have frequently been developed and used 3 . In Kyushu, located in southern Japan, rice and livestock have been raised in warm weather.…”
Section: Introductionmentioning
confidence: 99%